EXPLORING THE EMERGING NON-STANDARD ENGLISH PRONUNCIATION FEATURES OF L1 JAVANESE AND INDONESIAN SPEAKERS - Butarbutar, Octavia; Ekarina, Ekarina (Journal of English Language and Culture, 2024)
This study is concerned with pronunciation features of English learners whose L1 are Indonesian and Javanese. Specifically, the research views these non-standard pronunciation features as innovations by L2 English speakers, not as errors; and considers features of the speaker’s multi-linguistic repertoire as equal candidates that may win out and manifest themselves in the speaker’s spoken production. Consequently, data analysis undertaken expands beyond just contrastive analysis involving L1 transfer, and includes other cognitive factors that might influence the emergence of non-standard L2 pronunciation. To do this, the researchers watched a recorded video of international conference presentations available on youtube. Salient non-standard pronunciation features were then noted and compared with the standard English; this involves data on the  monophthongization of English diphthongs and the replacement of the consonants /ð/ and /θ/ with the plain /d/ and /t/.This data was compiled for different speakers, and was then analysed to uncover possible factors that influence the emergence of the non-standard pronunciation features. It can be concluded that L1 phonology, frequency, word spelling and general articulatory factors all play a role in potentially shaping a speaker’s L2 pronunciation features. The study also uncovers that while there are differences between speakers, individual speakers tend to be constant in their choice of non-standard pronunciation features.